2018
DOI: 10.1038/s41467-018-03765-0
|View full text |Cite
|
Sign up to set email alerts
|

Tuning defects in oxides at room temperature by lithium reduction

Abstract: Defects can greatly influence the properties of oxide materials; however, facile defect engineering of oxides at room temperature remains challenging. The generation of defects in oxides is difficult to control by conventional chemical reduction methods that usually require high temperatures and are time consuming. Here, we develop a facile room-temperature lithium reduction strategy to implant defects into a series of oxide nanoparticles including titanium dioxide (TiO2), zinc oxide (ZnO), tin dioxide (SnO2),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
232
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 503 publications
(255 citation statements)
references
References 60 publications
11
232
0
Order By: Relevance
“…According to the binary phase diagrams (Figure S5, Supporting Information), Pb is easy to form Pb–Li alloy with the presence of Li, which can help the reduced PZT layer adhere tightly on the surface of Li metal anode with good reproducibility. Studies have shown that when Li partially reduces metal oxide, lithium oxide passivation layer will be produced at the interface of metal oxide and Li . The lithium oxide passivation layer at the interface of reduced PZT and Li foil should also have promote the adhesion.…”
Section: Resultsmentioning
confidence: 99%
“…According to the binary phase diagrams (Figure S5, Supporting Information), Pb is easy to form Pb–Li alloy with the presence of Li, which can help the reduced PZT layer adhere tightly on the surface of Li metal anode with good reproducibility. Studies have shown that when Li partially reduces metal oxide, lithium oxide passivation layer will be produced at the interface of metal oxide and Li . The lithium oxide passivation layer at the interface of reduced PZT and Li foil should also have promote the adhesion.…”
Section: Resultsmentioning
confidence: 99%
“…O 1s signals are multicomponent, with the most intense peak at 530.3 eV due to oxygen in TiO 2 , and the less intense components at 531.5 and 532.6 eV due to -OH and/or defective oxygen and to adsorbed water, respectively. 23,38,39 Only the component at about 530 eV was considered to calculate O/Ti 4+ ratio, and it was found that the O/Ti 4+ ratios in A1 and A3 samples are 1.8 (AE0.2). The absence of reduced Ti was also noticed when HSGT-v was annealed in nitrogen or in hydrogen/nitrogen mixtures for different times (Fig.…”
Section: Surface and Electronic Characterizationmentioning
confidence: 99%
“…The electrons in these sites can be excited into the CB either by a thermal or photoexcitation process to form the unoccupied states [46,47]. Correspondingly, the herein observed marked colour change can also be ascribed to enhanced absorption of the visible and near-infrared light by Ti 3+ surface states in blue-TiO 2 NWs [48].…”
Section: Mapbi 3 /Blue-tio 2 Nws-based Visible Light Photodetectormentioning
confidence: 64%